2017
DOI: 10.20884/1.agrin.2017.21.1.334
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Dan Keeratan Hubungan Komponen Hasil Bawang Merah Kultivar Super Philip Di Sembilan Pemupukan

Abstract: ABSTRAKBawang merah merupakan salah satu komoditas penting di Indonesia. Tanaman ini dapat beradaptasi dengan berbagai kondisi lingkungan. Super Philip merupakan salah satu kultivar bawang merah nasional di Indonesia dengan potensi produktivitas sekitar 17,6 t/ha. Informasi tentang hubungan karakter dalam kultivar ini belum banyak dipelajari. Hubungan antara karakter penting dalam pengembangan kultivar sehingga dapat menerapkan teknologi baru untuk meningkatkan hasil secara langsung atau tidak langsung. Peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In addition, the high yield obtained in treatment B was also supported by the weight of the stover per clump and the weight of the bulbs per clump. Aziz et al [14] reported that the weight of the stover is one of the characters that can directly increase the weight of the shallot bulbs. The results of research by Hamdani and Susanto [15] showed that there was a strong correlation between the weight of the stover and the weight of bulbs per clump of shallots.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the high yield obtained in treatment B was also supported by the weight of the stover per clump and the weight of the bulbs per clump. Aziz et al [14] reported that the weight of the stover is one of the characters that can directly increase the weight of the shallot bulbs. The results of research by Hamdani and Susanto [15] showed that there was a strong correlation between the weight of the stover and the weight of bulbs per clump of shallots.…”
Section: Resultsmentioning
confidence: 99%